Analysis of Ethics and Law in Handling Cases of Maternal and Newborn Mortality in Indonesia - Agustina, Agustina; Jalaludin Harun (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Maternal and newborn mortality (MBR) is a serious public health problem in Indonesia. Maternal and newborn mortality rates are still high, although they have shown a downward trend in recent years. The factors contributing to MBR are complex and multidimensional, including social, economic, cultural, and legal factors. This research aims to analyze ethics and law in handling cases of maternal and newborn mortality in Indonesia. Methods: This research uses a qualitative method with a descriptive-analytical approach. Data was collected through literature studies, interviews with 15 key informants, and analysis of policy documents. Results: The research results show that there are several ethical and legal dilemmas in handling cases of maternal and newborn mortality in Indonesia. These ethical dilemmas include informed consent, confidentiality, and end-of-life care. Legal dilemmas relate to patient rights, professional responsibilities, and death investigations. Conclusion: Ethical and legal analysis in handling cases of maternal and newborn mortality in Indonesia is very important to ensure that patients receive quality and dignified care. Increasing health workers' knowledge and understanding of ethical and legal aspects can help reduce maternal and newborn mortality rates in Indonesia.